2013 IEEE 13th International Conference on Rehabilitation Robotics (ICORR) 2013
DOI: 10.1109/icorr.2013.6650487
|View full text |Cite
|
Sign up to set email alerts
|

Non-contact versus contact-based sensing methodologies for in-home upper arm robotic rehabilitation

Abstract: In recent years, robot-assisted rehabilitation has gained momentum as a viable means for improving outcomes for therapeutic interventions. Such therapy experiences allow controlled and repeatable trials and quantitative evaluation of mobility metrics. Typically though these robotic devices have been focused on rehabilitation within a clinical setting. In these traditional robot-assisted rehabilitation studies, participants are required to perform goal-directed movements with the robot during a therapy session.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Once the baseline is computed, the algorithm compares the user's ROM values to their respective baselines. The algorithm computes a difference percent error normalized by the corresponding joint's maximum capacity (7). where ROMj,user is the user's ROM for joint j, ROMj,baseline is the ROM computed by the kinematic model for joint j, and ROMj,max is the maximum angle capacity for joint j (obtained by making a full joint movement).…”
Section: Range Of Motionmentioning
confidence: 99%
“…Once the baseline is computed, the algorithm compares the user's ROM values to their respective baselines. The algorithm computes a difference percent error normalized by the corresponding joint's maximum capacity (7). where ROMj,user is the user's ROM for joint j, ROMj,baseline is the ROM computed by the kinematic model for joint j, and ROMj,max is the maximum angle capacity for joint j (obtained by making a full joint movement).…”
Section: Range Of Motionmentioning
confidence: 99%
“…It is reported that the impact of students' cognitive emotions during interactions with different computer-based learning environments can be rather frustrating than boring [10]. Thus, it is essential to observe the mental health of the subject for HMI application as it could affect the self-confidence of the subject and recovery period [11] through their emotion.…”
Section: Co-published By Atlantis Press and Taylor And Francis Copyrighmentioning
confidence: 99%
“…On the other hand, there is an increasing need for occupational therapists to assist patients with a wide range of exercises, so these devices can be used as remote rehabilitation systems to reduce the therapists’ workload [ 7 ]. Research also shows that remote rehabilitation can have several potential advantages, such as keeping patients engaged beyond the clinical context and tracking and assessing movements when they are at home [ 8 ]. Moreover, remote rehabilitation has the potential to reduce healthcare costs [ 7 ] by eliminating the need for patients to travel to physical therapy appointments and by reducing the need for in-person therapy sessions.…”
Section: Introductionmentioning
confidence: 99%